Appropriate Technology Development for Energy Conservation in Animal Husbandry in the Context of Southeast Asian Countries - Das, Arup R.; Sayanno, Tasriba K.; Khandaker, Nadim R. (Journey for Sustainable Development and Peace Journal, 2023)
Climate change is a global issue causing adverse effects in different sectors all over the world. Nations in Southeast Asia are mostly developing nations and do not have adequate resources to tackle the catastrophic effects of climate change. An increase in greenhouse gas emissions led to a significant rise in temperature all over the world, which is more vivid in Southeast Asian nations as they are tropical countries. Many residents of rural areas in these nations rely on agriculture and animal husbandry as means of their income. Over the last decade, farmers and poultry owners have faced more challenges to mitigate the extreme temperatures in which livestock cannot survive. Additionally, depleting fossil fuel levels, rise in the price of commodities and frequent power outages only add to the problem. Thus, a new environmentally friendly sustainable strategy has been proposed which makes use of renewable energy. The study also focuses on energy conservation technologies and techniques that the farmers can implement. If farmers and poultry owners are able to control the ambient temperature of the livestock housing, they are more likely to stay in business because of more profits. This temperature control can be acquired from livestock wastes, which the farmers usually dispose, of by generation of heat and electricity. This not only promotes the use of green technology but also reduces pollution associated with these wastes creating a more hygienic environment, producing more power, and enhancing the economy while aligning with sustainable development goals.